An influenza A vaccine based on the extracellular domain of matrix 2 protein protects BALB/C mice against H1N1 and H3N2 - Ong, Hui Kian; Yong, Chean Yeah; Tan, Wen Siang; Yeap, Swee Keong; Omar, Abdul Rahman; Abdul Razak, Mariatulqabtiah; Ho, Kok Lian (MDPI, 2019)
Current seasonal influenza A virus (IAV) vaccines are strain-specific and require annual reconstitution to accommodate the viral mutations. Mismatches between the vaccines and circulating strains often lead to high morbidity. Hence, development of a universal influenza A vaccine targeting all IAV strains is urgently needed. In the present study, the protective efficacy and immune responses induced by the extracellular domain of Matrix 2 protein (M2e) displayed on the virus-like particles of Macrobrachium rosenbergii nodavirus (NvC-M2ex3) were investigated in BALB/c mice. NvC-M2ex3 was demonstrated to be highly immunogenic even in the absence of adjuvants. Higher anti-M2e antibody titers corresponded well with increased survival, reduced immunopathology, and morbidity of the infected BALB/c mice. The mice immunized with NvC-M2ex3 exhibited lower H1N1 and H3N2 virus replication in the respiratory tract and the vaccine activated the production of different antiviral cytokines when they were challenged with H1N1 and H3N2. Collectively, these results suggest that NvC-M2ex3 could be a potential universal influenza A vaccine.